IL-1 receptor antagonist attenuates neonatal lipopolysaccharide-induced long-lasting learning impairment and hippocampal injury in adult rats. Issue 1 (2nd April 2015) - Lan, Kuo-Mao; Tien, Lu-Tai; Pang, Yi; Bhatt, Abhay J.; Fan, Lir-Wan
Highlights IL1-ra attenuates neonatal LPS induced learning deficits in rats. IL1-ra attenuates neonatal LPS induced hippocampal injury in rats. IL1-ra protects against neonatal LPS induced chronic neuroinflammation in rats.